Optimal Sizing of Hybrid Battery - Supercapacitor - Generator System in Electric Ship using Genetic Algorithm - Sorn, Chanraksa; Lystianingrum, Vita; Santoso, Agoes (International Journal of Marine Engineering Innovation and Research, 2025)
The fossil fuel emissions from the ship have significant impacts on climate change, environmental quality, and human health. The marine sector has consequently grown increasingly interested in implementing greener and more sustainable energy solutions. The electric propulsion ship is powered by hybrid energy storage has the ability to lower emissions, improve the power quality, and lower fuel consumption. There are many types of energy storage system such as battery, supercapacitor, hydrogen, etc. In this study, the combine of battery and supercapacitor are chosen as a hybrid energy storage system to supply power to the electric ship and diesel generator is an additional power source. The main objective is to sizing the hybrid energy storage system to minimize the total cost while maintaining reliable energy supply. The optimal sizing of each component is conducted in MATLAB using Genetic Algorithm.